2009
DOI: 10.3386/w14817
|View full text |Cite
|
Sign up to set email alerts
|

Do Newspapers Matter? Short-run and Long-run Evidence from the Closure of The Cincinnati Post

Abstract: The Cincinnati Post published its last edition on New Year's Eve 2007, leaving the Cincinnati Enquirer as the only daily newspaper in the market. The next year, fewer candidates ran for municipal office in the Kentucky suburbs most reliant on the Post, incumbents became more likely to win reelection, and voter turnout and campaign spending fell. These changes happened even though the Enquirer at least temporarily increased its coverage of the Post's former strongholds. Voter turnout remained depressed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…From a comparative perspective, our results are also relevant for the debate on competition and localism in the US. 48 Indeed, the present analysis provides supporting evidence to the claim that promoting localism and competition in the market for news may have positive effects on electoral participation and on the performance of local governments.…”
Section: Resultssupporting
confidence: 51%
“…From a comparative perspective, our results are also relevant for the debate on competition and localism in the US. 48 Indeed, the present analysis provides supporting evidence to the claim that promoting localism and competition in the market for news may have positive effects on electoral participation and on the performance of local governments.…”
Section: Resultssupporting
confidence: 51%
“…A recent study of Cincinnati and its suburbs (Schulhofer-Wohl & Garrido, 2011) that evaluated the effects of the 2007 closure of the Cincinnati Post also used this kind of community-level approach. The authors suggested that a number of negative political outcomes could be observed from 2007-2010 in the northern Kentucky communities that the Post traditionally served.…”
Section: Empirical Evidence Of Local Newspapers' Importancementioning
confidence: 99%
“…One potential threat that elected officials may be concerned about is critical media coverage. Studies have found that coverage levels of politicians vary widely (Arnold 2004;Campante and Do 2013) and that those differences in coverage can have significant consequences for the incumbency advantage in elections (Prior 2006;Schulhofer-Wohl and Garrido 2009;Gentzkow, Shapiro, and Sinkinson 2011), legislator performance in office (Snyder and Strömberg 2010), and possibly even state-level patterns of corruption (Campante and Do 2013). Fact-checking thus has the potential to create career risks for politicians by generating negative coverage for politicians that could damage their reputation and credibility.…”
Section: The Effect Of Fact-checking On Politiciansmentioning
confidence: 99%